Multiplicity of forced oscillations for scalar retarded functional differential equations. (9th January 2018) - Calamai, Alessandro; Pera, Maria Patrizia; Spadini, Marco
Abstract : We find multiplicity results for forced oscillations of a periodically perturbed autonomous second‐order equation, the perturbing term possibly depending on the whole history of the system. The techniques that we use are topological in nature, but the technical details are hidden in the proofs and completely transparent to the reader only interested in the results.